2019
DOI: 10.1038/s41598-019-47155-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of spent FCC catalyst composites by loaded V2O5 and TiO2 and their comparative photocatalytic activities

Abstract: The spent fluid catalytic cracking catalyst (FCC) has been loaded with different content of V 2 O 5 and TiO 2 through a modified-impregnation method. X-ray Diffraction (XRD), ultraviolet-visible spectrophotometry (UV-Vis), Scanning Electron Microscope (SEM), and Fourier Transform Infrared spectroscopy (FT-IR) are used to characterize the structure and morphology of these samples. Their photocatalytic activity was evaluated by degradation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…But the XRD interplanar spacing (d) of PI fibre changes as the concentration of MFA changes. In Table 1, there is a slight increase in interplanar spacing at 14.49° and 22.30° with an increase in the concentration of MFA, indicating that the spaces between the molecular chains of these two crystal planes are larger after introducing MFA into PI fibre 26 . These results show that swelling agents can improve the dyeability of PI fibres by expanding the space between molecular chains, resulting in easier penetration of dyes.…”
Section: Resultsmentioning
confidence: 83%
“…But the XRD interplanar spacing (d) of PI fibre changes as the concentration of MFA changes. In Table 1, there is a slight increase in interplanar spacing at 14.49° and 22.30° with an increase in the concentration of MFA, indicating that the spaces between the molecular chains of these two crystal planes are larger after introducing MFA into PI fibre 26 . These results show that swelling agents can improve the dyeability of PI fibres by expanding the space between molecular chains, resulting in easier penetration of dyes.…”
Section: Resultsmentioning
confidence: 83%
“…Spent hydroprocessing catalysts has been used in construction, ceramic and refractory applications [41]. In reality, because SFCCR is predominantly made up of silica and alumina, it possesses a steady molecular sieve arrangement that has a lot of surface area and might be used as a catalytic support [42]. The findings demonstrated that CO 2 functioned as an additional catalyst, enhancing the transfer of mass and regulating the pH within the range of 3.54 to 3.91.…”
Section: Pimaric Acidmentioning
confidence: 99%
“…However, the conduction band of V 2 O 5 rises, becoming higher than the conduction band of TiO 2 , which represents a driving force for the transport of electrons from V 2 O 5 to TiO 2 , and the transport of holes from TiO 2 to V 2 O 5 . This cascade distribution of energy bands improves charge carrier separation, thus decreasing recombination and losses during photocatalysis [13].…”
Section: Introductionmentioning
confidence: 99%